Feasibility of optimizing intensity‐modulated radiation therapy plans based on measured mucosal dose adjacent to dental fillings and toxicity outcomes. (9th July 2018) - Seol, Seung Won; Aggarwal, Sonya; von Eyben, Rie; Wang, Ziwei; Chan, Cato; Say, Carmen; Xing, Lei; Hara, Wendy; Yang, Yong; Le, Quynh Thu
Abstract: We prospectively investigated the feasibility of IMRT treatment plan optimization based on dosimeter measurements of lateral tongue mucosal dose adjacent to the dental fillings and evaluated dose‐toxicity relationship and factors affecting oral mucositis (OM) in head and neck cancer patients. Twenty‐nine head and neck cancer patients with metallic dental fillings who were scheduled to undergo fractionated external beam radiation therapy (RT) ± chemotherapy were enrolled. The lateral tongue dose was measured and if the calculated dose for the entire treatment was ≥35 Gy, a re‐plan was generated to reduce the lateral tongue mucosal dose. OM was graded weekly according to Common Terminology Criteria for Adverse Events version 4.0 and the patients completed the Oral Mucositis Weekly Questionnaire‐Head and Neck Cancer. The result showed that it was not feasible to optimize the IMRT plan based on measured tongue dose in most of the patients who needed re‐plan as re‐planning compromised the target coverage in 60% of these patients. The duration of grade (Gr) 2 OM was correlated with measured lateral tongue dose ( P = 0.050). Concurrent cetuximab was significantly associated with faster onset of Gr2 OM than concurrent cisplatin ( P = 0.006) and with longer duration of OM ( P = 0.041) compared to concurrent cisplatin or IMRT‐alone. The pattern of reported pain over time was significantly different for each treatment type (RT and cetuximab, RT and cisplatin and RT‐alone) and depending on the dose level ( P = 0.006). In conclusion, optimizing the IMRT plan based on measured lateral tongue dose was not feasible. Measured lateral tongue dose was significantly correlated with longer duration of OM ≥Gr2, and concurrent cetuximab was associated with earlier onset and longer duration of OM ≥Gr2.